Hubungan Pengetahuan dan Budaya dengan Terapi Uap Panas (Peusale) Pada Ibu Nifas di Kecamatan Lhoknga Kabupaten Aceh Besar Tahun 2021 - Putri Kurniawati (Journal of Pharmaceutical and Health Research, 2022)
Back ground data obtained from the lhoknga publik helth center in 2018 AKI 0f 453 people and IMR of 4 people, in 2019 AKI of 8 people in 2020 AKI of 11 people in IMR of 2 people a total of 480 pospartum care is on effort mode by midwives, pospartum mothers and famillies with the aim that the nutritional needs of postpartum mothers are fulfillid, personal hygiene is maintained. Research objectives to dermine the relationship between knaowledge and the influence of cultur with hot steam therapy (peusale) on postpartum mothers in lhoknga district, aceh besar regency 2021. This research method used the method the analytikal cross sectional approach wich was carried out on september 14-19-2021 was carried out in the lhoknga sub-district. The population in this study was all 31 postpartum mothers. Sampling using total sampling data analysis using univariatee and bivariate analysis with the chi-squer test method showed a p-value of 0.000 0.05 research results. The results of statistical resets wit chi-squer test showed a p-value of 0.000<0.05, meaning that there was an influence of knowledge with peusale steam therapy culture. Besed on the chi-squer thes table shows a p-value of 0.001<0.05, there is an influence between culture and steam therapy for postpartum mothers in lhoknga district, aceh besar district